Green energy projects in households and its financial support in Ukraine - Sotnyk Iryna; Kurbatova Tetiana; Dashkin Vitalii; Kovalenko Yevgen (International Journal of Sustainable Energy, 2020)
The paper deals with the solar energy promotion in households in Ukraine. Despite the positive dynamics of solar power plants construction, today the share of electricity, generated on their basis, in the country’s electricity mix remains insignificant. The main reason for this is the need for essential start-up investments. Since the economic efficiency of investment projects depends on installed capacity of plants, the structure and cost of the project financing sources; the paper focuses on estimation of financial sustainability of solar photovoltaic power plants construction under the credit programme ‘Eco-Energy’. The obtained results show the high profitability of own and credit resources’ investment in the considered projects that varies from 78.91% for the 10 kW solar power plants to 128.04% for the 30 kW ones. On this basis, policy recommendations for improving financing and other economic mechanisms to enhance renewable energy development in Ukrainian households have been developed.